1980
DOI: 10.4319/lo.1980.25.5.0952
|View full text |Cite
|
Sign up to set email alerts
|

Processing of confined and naturally entrained leaf litter in a woodland stream ecosystem1

Abstract: A comparison between stream community processing rates of naturally entrained leaf litter and leaves in packs or 1‐mm‐mesh bags demonstrated that packs served as a suitable analogue of processing in exposed sites (riffles) whereas bags did not. In riffles, leaves in bags were processed at rates characteristic of litter in depositional zones (pools and alcoves). A length‐weight regression method for evaluating the range of microhabitat‐related processing rates in stream communities appears suitable. Leaf litter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
8
2

Year Published

1981
1981
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 8 publications
0
52
8
2
Order By: Relevance
“…VFBOM) in C53 compared with C55, in terms of higher standing crops and lower ash content, may have contributed to higher levels of chironomid production. Several studies have reported positive relationships between densities of various stream invertebrates and apparent food availability (Hawkins, 1986;Hawkins, Murphy & Anderson, 1982;Cummins et al, 1980;Drake, 1982). However, in the present study, only the densities of chironomids collected on the rock outcrops and those from the benthic cores in C53 showed a positive relationship with standing crops of VFBOM.…”
Section: Discussioncontrasting
confidence: 55%
“…VFBOM) in C53 compared with C55, in terms of higher standing crops and lower ash content, may have contributed to higher levels of chironomid production. Several studies have reported positive relationships between densities of various stream invertebrates and apparent food availability (Hawkins, 1986;Hawkins, Murphy & Anderson, 1982;Cummins et al, 1980;Drake, 1982). However, in the present study, only the densities of chironomids collected on the rock outcrops and those from the benthic cores in C53 showed a positive relationship with standing crops of VFBOM.…”
Section: Discussioncontrasting
confidence: 55%
“…In forested watersheds, litter fall plays a n important role as a source of organic matter in headwaters. It represents about 200 g C m-' channel area yr-' (range 25 to 400) (Dawson 1976, Bell 1978, Cummins et al 1980, Herbst 1980), making about 0.8 kg C km-2 watershed d-'. The C:N:P (molar) composition of this material is 1250:16:1 (Meybeck 1982).…”
Section: Constraints Characterizing the Scenariosmentioning
confidence: 99%
“…Nevertheless, it is well established that invertebrate shredders can have an important role in processing leaf litter (Cummins et al 1980;Collier & Winterbourn 1987;Bird & Kaushik 1992), and that shredders (e.g., Anisocentropus kirramus: Nolen & Pearson 1993), scraper-grazers (e.g., Potamopyrgus jenkinsi : Hanlon 1981), and collectors (e.g., Gammarus pseudolimnaeus: Bird & Kaushik 1985) select particular kinds of leaves over others as food. This may be for a variety of reasons including the structure, chemistry, and toughness of the leaf, and also its degree of microbial conditioning and associated decomposition (Petersen & Cummins 1974;Irons et al 1988;Barlocher & Newell 1994).…”
Section: Introductionmentioning
confidence: 99%